2021
DOI: 10.1155/2021/4914371
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Pediatric COVID-19 Epidemiology and Clinical Characteristics

Abstract: Background. Despite the worldwide spread of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2), information about the epidemiological and clinical patterns of this infection is still largely unknown in children. In addition, the prevalence of this disease is still very high in some parts of the world, including Iran. Thus, this study aims to evaluate the epidemiological features, laboratory and imaging findings, and the type of treatments in children with novel coronavirus 2019 (COVID-19). Method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…It was found that the most common symptoms reported in children, i.e., <18 years old, are cough and dyspnea ( Rabizadeh et al, 2020 ; Fahimzad et al, 2021 ) and fever and cough ( Hosseninasab et al, 2020 ; Mahmoudi et al, 2020 ; Armin et al, 2021 ; Hoseinyazdi et al, 2021 ; Mamishi et al, 2021 ; Soleimani et al, 2021 ; Keshavarz Valian et al, 2022 ). Gastrointestinal symptoms including vomiting, nausea, and diarrhea were reported but to a lesser extent ( Hosseninasab et al, 2020 ; Mamishi et al, 2020 ; Armin et al, 2021 ; Fahimzad et al, 2021 ; Pourakbari et al, 2021 ). Interestingly, neurological symptoms such as seizure, fatigue, and headache were also described ( Cheraghali et al, 2021 ; Fahimzad et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the most common symptoms reported in children, i.e., <18 years old, are cough and dyspnea ( Rabizadeh et al, 2020 ; Fahimzad et al, 2021 ) and fever and cough ( Hosseninasab et al, 2020 ; Mahmoudi et al, 2020 ; Armin et al, 2021 ; Hoseinyazdi et al, 2021 ; Mamishi et al, 2021 ; Soleimani et al, 2021 ; Keshavarz Valian et al, 2022 ). Gastrointestinal symptoms including vomiting, nausea, and diarrhea were reported but to a lesser extent ( Hosseninasab et al, 2020 ; Mamishi et al, 2020 ; Armin et al, 2021 ; Fahimzad et al, 2021 ; Pourakbari et al, 2021 ). Interestingly, neurological symptoms such as seizure, fatigue, and headache were also described ( Cheraghali et al, 2021 ; Fahimzad et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
“…In COVID-19 children, compared to those admitted to the general ward, ICU patients had more acute respiratory distress syndrome, shock, and acute cardiac injury as complications ( Fahimzad et al, 2021 ). The mortality rate appears to be low in infected children of Iran ( Hosseninasab et al, 2020 ; Armin et al, 2021 ; Hoseinyazdi et al, 2021 ; Mamishi et al, 2021 ; Pourakbari et al, 2021 ), ranging from 0 death ( Esmaeili Dooki et al, 2020 ; Soleimani et al, 2021 ) to 11% ( Mahmoudi et al, 2020 ; Mamishi et al, 2020 ; Armin et al, 2021 ). Interestingly, in one study the mortality rate was 20%, however, this was in children with underlying malignancies, namely acute lymphocytic and acute myeloid leukemia ( Navaeian et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
See 3 more Smart Citations